Pemodelan Komponen Sistem Enterprise Resource Planning pada Industri Produksi Minyak - Andry, Johanes Fernandes; Bernadus Gunawan Sudarsono; Francka Sakti Lee; Vania Christy; Lydia Liliana (Fakultas Teknik Universitas Hamzanwadi, 2024)
The digitalization of technology in the current era of globalization has brought many changes to the industry. The emergence of Enterprise Resource Planning (ERP) functions to integrate all departments and industrial business functions, especially in the oil production sector. ERP systems simplify business processes by integrating key functions from various departments. The business processes in the oil production industry are currently not yet running, which has given rise to problems with errors in purchasing goods from suppliers, inaccurate calculations of raw material usage, raw material stocks not being updated quickly, and purchasing reports not being generated automatically. Based on the background of these problems, the industry requires a component modeling that helps the ERP implementation process. Component modeling allows users in industry to understand ERP systems better without being overwhelmed by product or technical details. This research aims to define the ERP system components that are taken into consideration in its implementation. The research stages are divided into five, namely pre-implementation, analysis, design, construction and implementation. The results of the research are component model designs in terms of software, process flow, user mindset, and change management that will be used in implementing the ERP system